Chatbots for embarrassing and stigmatizing conditions: could chatbots encourage users to seek medical advice? - Branley-Bell, Dawn; Brown, Richard; Coventry, Lynne; Sillence, Elizabeth (Frontiers in Communication, 2023)
Chatbots are increasingly being used across a wide range of contexts. Medical chatbots have the potential to improve healthcare capacity and provide timely patient access to health information.Chatbots may also be useful for encouraging individuals to seek an initial consultation for embarrassing or stigmatising conditions. This experimental study used a series of vignettes to test the impact of different scenarios (experiencing embarrassing vs stigmatising conditions, and sexual vs non-sexual symptoms) on consultation preferences (chatbot vs doctor), attitudes towards consultation methods, and expected speed of seeking medical advice. The findings show that the majority of participants preferred doctors over chatbots for consultations across all conditions and symptom types. However, more participants preferred chatbots when addressing embarrassing sexual symptoms, compared with other symptom categories.Consulting with a doctor was believed to be more accurate, reassuring, trustworthy, useful and confidential than consulting with a medical chatbot, but also more embarrassing and stressful.Consulting with a medical chatbot was believed to be easier and more convenient, but also more frustrating. Interestingly, people with an overall preference for chatbots believed this method would encourage them to seek medical advice earlier than those who would prefer to consult with a doctor. The findings highlight the potential role of chatbots in addressing embarrassing sexual symptoms. Incorporating chatbots into healthcare systems could provide a faster, more accessible and convenient route to health information and early diagnosis, as individuals may use them to seek earlier consultations.